NILAI ESTETIKA DALAM UNGKAPAN ADAT MELAYU RIAU KARYA TENAS EFFENDY SUNTINGAN MAKMUR HENDRIK DAN KAWAN-KAWAN - Muhammad Nassarudin; Sumiharti Sumiharti; Erlina Zahar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is aimed at describing the aesthetics values that are found in the expression of Riau Malay Custom by Tenas Effendy in the book Tegak Menjaga Tuah, Duduk Memelihara Marwah edited by Makmur Hendrik and friends. Aesthetics value is the element of beauty in literary work and it is a phenomenon of flowers and smells. The beauty is created byan author with language tools through particular language exploration where the author shows the aspects of beauty optimally. This research is qualitative descriptive by using structural and stylistic. The data is taken from aesthetics values in the expression of Riau Malay by Tenas Effendy in the book Tegak Menjaga Tuah, Duduk Memelihara Marwah edited by Makmur Hendrik and friends. Moreover, the conclusion is made besd on the expressions found in that book. Based on the analysis, it can be concluded that Tegak Menjaga Tuah, Duduk MemeliharaMarwah book edited by Makmur Hendrik and friends comprises 25 expressions of aesthetic values of Riau Malay. Key Words: aesthetic values, Riau Malay expression